Everything Here is Fine: Protective Buffering by Military Spouses During a Deployment. Issue 3 (28th June 2019) - Carter, Sarah P.; Renshaw, Keith D.; Allen, Elizabeth S.; Markman, Howard J.; Stanley, Scott M.
Abstract : To minimize potential distractions for deployed military service members (SMs), some nondeployed romantic partners have reported engaging in protective buffering, or intentionally withholding information or concerns to protect their deployed partner. This study assessed the associations of protective buffering and psychological distress and marital satisfaction for military couples during and after deployment. Additionally, the study explored whether protective buffering was related to SM reports of being distracted during deployment by family matters. A total of 54 couples provided data before, during, and after an Army deployment. In multilevel models, higher protective buffering by partners was associated with higher psychological distress and lower marital satisfaction for both SMs and partners during, but not after, deployment. Additionally, partners reported frequent use of protective buffering during deployment; however, protective buffering was not significantly correlated with family related distraction for SMs during deployment. Limitations and implications of these findings are discussed. Abstract : Para minimizar posibles distracciones para miembros del servicio militar (SM) desplegados, algunas parejas románticas no desplegadas han informado que practican la amortiguación protectora, es decir, ocultan información o preocupaciones intencionalmente para proteger a su pareja desplegada. Este estudio evaluó las asociaciones de amortiguación protectora y angustia psicológica y satisfacción conyugal para parejas militares durante y después del despliegue. Además, el estudio exploró si la amortiguación protectora tenía relación con informes de los SM de estar distraídos durante el despliegue por cuestiones familiares. Un total de 54 parejas proporcionó datos antes, durante y después de un despliegue del ejército. En modelos multinivel, una amortiguación protectora mayor por parte de las parejas se asoció a mayor angustia psicológica y menor satisfacción conyugal tanto para los SM como para las parejas durante, pero no después del despliegue. Además, los socios informaron el uso frecuente de amortiguación protectora durante un despliegue; sin embargo, la amortiguación protectora no tuvo una correlación significativa con la distracción por motivos familiares para los SM durante el despliegue. Se discuten las limitaciones e implicaciones de estos hallazgos. Abstract : 为了减少对服役期间的军人受到的潜在干扰, 有些非从军的情侣们报告了他们采取了缓冲性保护措施, 即刻意地隐瞒一些事情或忧虑之事不让在部队服役的一方知道太多家里的事情以期达到对他们的保护的目的。本研究旨在考察军人伴侣中在一方去部队服役期间和退役之后, 保护性缓冲带来了什么样的影响, 主要是指和心理压力以及婚姻满意度之间的相关性。另外, 本研究也调查了保护性缓冲是否和服役人员自己在当兵期间报告的被家庭事务干扰之间有一定关联。参与调查研究的军人伴侣有54对, 数据的搜集的时间段包括在当兵前期, 服役中和退役期间。多级模型显示, 从军者和其伴侣在当兵的一方服役期间, 越高的保护性缓冲和越高的心理困扰以及越低的婚姻满意度相关联, 结束兵役之后并没有这样的关联。而且, 军人伴侣报告在当兵的一方服役期间使用保护性缓冲更频繁, 但是保护性缓冲措施并没有和当兵的一方在服役期间受到的和家事相关的干扰有很明显的关联性。本研究的局限性和启示意义有所讨论。